(untitled) (Scientific journal of the Fergana State University, 2024)
Punctuation is an important component of written language that helps convey meaning and facilitates effective communication. In social settings such as online chats, social media platforms, and messaging apps, punctuation plays a crucial role in shaping the tone, intent, and overall pragmatics of a message. This article explores the importance of punctuation in social settings and highlights its impact on conveying emotion, clarifying intent, and avoiding misinterpretation.